Complete mitochondrial genome of Pseudogastromyzon fasciatus (Osteichthyes: Gastromyzontidae). Issue 1 (1st January 2016) - Song, Xiaojing; Yang, Yang; Tang, Wenqiao
Abstract: Pseudogastromyzon fasciatus belonging to the family Gastromyzontidae is a good model for phylogeny and zoogeography research. The complete mitochondrial genome of P. fasciatus was sequenced in this study. The genome sequence is 16, 563 bp in length, comprising 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and one control region. Overall base composition is 29.70% A, 25.16% T, 16.53% G, and 28.60% C. The result of phylogenetic analysis indicates that P. fasciatus mitogenome is close to that of P. myersi .